2013
DOI: 10.1097/aci.0000000000000009
|View full text |Cite
|
Sign up to set email alerts
|

B-cell memory and primary immune deficiencies

Abstract: IL-21 is a key cytokine in development of B-cells into immunoglobulin-secreting cells. Abnormal signalling through the IL-21R/γc/JAK3/STAT3 pathway leads to defective humoral immune responses to both T-dependent and T-independent antigens and impairs the establishment of long-lasting B-cell memory. Studies involving patients with hyper-IgE syndrome demonstrated the nonredundant role of STAT3 in B-cell production of high-affinity specific antibodies, while total serum immunoglobulins could be maintained through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…A downregulation of IL21R might play a role in the persistence of colonization during the primary E. coli O157:H7-infection and re-infection of the host, since the IL-21-IL-21R pathway is important in the development of immune responses, as abnormal signaling through the IL-21R/γc/JAK3/STAT3 pathway leads to defective humoral immune responses to both T-dependent and T-independent antigens and impairs the establishment of long-lasting B-cell memory [52]. A bacterial infection can elicit IgM memory B-cells which requires T cell- dependent and IL-21R signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A downregulation of IL21R might play a role in the persistence of colonization during the primary E. coli O157:H7-infection and re-infection of the host, since the IL-21-IL-21R pathway is important in the development of immune responses, as abnormal signaling through the IL-21R/γc/JAK3/STAT3 pathway leads to defective humoral immune responses to both T-dependent and T-independent antigens and impairs the establishment of long-lasting B-cell memory [52]. A bacterial infection can elicit IgM memory B-cells which requires T cell- dependent and IL-21R signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Thus B cell receptor (BCR) activation induces B cell apoptosis, even enhanced by IL-21, if survival signals provided through CD40 contact are absent. Accordingly, the stimulatory/inhibitory effect of IL-21 depends on the accompanying signal and the B cell subpopulation evaluated 17 , 18 . We previously demonstrated that memory B cell loss in a CVID patients’ subgroup (with compromised memory B cell compartment) could be the consequence of increased susceptibility to activation-induced apoptosis 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a selective failure of immune tolerance to specific mitochondrial autoantigens in primary biliary cirrhosis (PBC), and systemic evidence of B‐cell dysregulation, there is a paucity of data that provide a mechanistic explanation of these abnormalities of B‐cell immune responses. Clearly, there are multiple factors that regulate B‐cell homeostasis, including activation of B‐cell receptors, interaction with multiple coreceptors, and interactions with the local cytokine microenvironment . The lymphoid microenvironment is particularly critical for B‐cell proliferation and differentiation as well as fulfilling a requirement for establishment of an enduring immune response.…”
mentioning
confidence: 99%